Preference and performance of Polymorphomyia basilica on different phenotypes of Chromolaena odorata and other Asteraceae in the laboratory - Mahlobo, Thandeka; Dube, Nontembeko; Zachariades, Costas; Munyai, Thinandavha Caswell (Frontiers in Agronomy, 2025)
Chromolaena odorata, a weed of neotropical origin, remains insufficiently controlled by biological means in South Africa. The stem-galling fly Polymorphomyia basilica was introduced as a potential agent and previously shown to be largely host-specific under no-choice conditions. This study conducted multichoice and no-choice trials to test five nontarget plant species previously selected by P. basilica in no-choice trials, and to assess the fly’s preference and performance on various C. odorata phenotypes, including the southern African biotype (SAB) and the Asian/West African biotype (AWAB). Survival and development rates of P. basilica were highest on C. odorata (SAB) and Ageratum conyzoides. Only a few galls produced adult flies on Stomatanthes africanus and Campuloclinium macrocephalum, and these adults showed low longevity. P. basilica displayed a strong preference for and high performance on C. odorata (SAB) in both trial types, with over 90% of progeny surviving to adulthood. Many larvae also developed successfully on the Taiwan 129/130 (AWAB) and Jamaican 117 phenotypes, whereas development was poorer on other phenotypes. Although the cause of variation among phenotypes remains unclear, the results indicate that P. basilica is a suitable biocontrol agent for C. odorata in South Africa and can sustain populations on the AWAB biotype where it is invasive.